Purification of Biotransformation Products of Cis-Isoflavan-4-ol by Biphenyl Dioxygenase of Pseudomonas pseudoalcaligenes KF707 Strain Expressed in Escherichia coli - Sulistiyani, Tri Ratna (UI Scholars Hub, 2013)
Isoflavone has multiple beneficial effects on human health, especially through its antioxidant and anticancer activities. The biotransformation of isoflavone using byphenyl dioxygenase could be performed to extend the diversity of flavonoids and to improve their biological and physiological properties. Biotransformation of two enantiomers (3R, 4R)-cis-isoflavan-4-ol and (3S, 4S)-cis-isoflavan-4-ol by E. coli JM109 (pJHF108) carrying a biphenyl dioxygenase gene from P. pseudoalcaligenes KF707 produced two products, designated as CM1 and CM2. The products had a retention time of 11.9 and 14.6 min, respectively, and the same absorption peaks at 204, 220, and 275 nm. CM1 and CM2 had [M-H2O+H]+ at m/z 225. Based on the molecular mass and hydrolysis products, we proposed that epoxidation occurred on cis-isoflavan-4-ol. Chloroform extraction instead of ethyl acetate extraction was performed to improve the stability of cis metabolites, CM1 and CM2.